Indoor Air Quality in Offices and Classrooms in Public Utility Building - a Case Study - Łuszczyńska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A microbiological analysis of indoor air quality in offices, lecture rooms, and hallways in a public utility building has been carried out in the Lubuskie Voivodship (Poland). In one of the storage rooms, the presence of fungi on the building partition was found in the place of water infiltration as a result of a technological failure in the building. A total of 17 nonresidential interiors were examined.
Keywords: indoor air quality; bioaerosol; microorganisms; fungi; jakość powietrza w pomieszczeniach; bioaerozol; mikroorganizmy; grzyby